INTERAKSI SOSIAL ASOSIATIF PADA ANAK BERKEBUTUHAN KHUSUS TUNAGRAHITA DI SEKOLAH LUAR BIASA DHARMA ASIH KOTA PONTIANAK - Laras, Dahni Swasti; Salim, Izhar; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This thesis entitled â€œsocial associative interaction in children with special needs mental retardation in Dharma Asih extraordinary school in Pontianak Cityâ€. The purpose of this research to describe the cooperation of harmony and cooptation cooperation in children with mental retardation in Dharma Asih Pontianak city. The method in this research is qualitative method with descriptive analysis. The techniques used with obtain data in this research are observation, interview and documentation. The subjects of this research are two students, one teacher and marching band coach. The result of this research show that the role this it can be seen from the observation that students who studying inside or outside the classroom is routine practice which is done after the learning progress, learnes look very harmonious. They help each other if one of the students have difficulties in doing the task and learnes able interaction with the marching band coach who has worked one yaer in the school means that the learn can reseive a new element from the marching band coach, therefore the cooptation cooperation between the students and the marching band coach goes well.Â Keywords: Associative Sosial Interaction, Mental RetardationÂ